O espaço geográfico do vale do rio Vacacaí-mirin no município de Santa Maria-RS - Mantelli, Jussara; Borin, Salete Rejane; Medeiros, Edgardo Ramos (Geografia Ensino & Pesquisa, 2016)
O espaço geográfico do vale do rio Vacacaí-mirin no município de Santa Maria-RS